A Novel Approach for Path Planning in Case Of Drones for Water Monitoring - Shiva Prasad, Mahesh Jujjavarapu, Prema C, Reddy Basha D, Manoj G (International Journal of Advanced Science and Technology, 2020)
With the expansion in the uses of drones, we have witnessed practically how valuable they are right from conveyance to surveillance autonomously. While there have been different studies to enhance the performance, for example, upgrading the sensors installed onboard, to obstacle evasion path planning techniques. We would like to work on a new approach of how water samples can be collected by environmental drones without pre-determined points for sampling contrary to current studies in water quality monitoring. Our approach is that, a drone captures air quality over the water body along with its coordinates in its initial flight with an IOT system on boarded. During the flight, the recorded data is classified based on the readings observed in real time. Our experimental results conducted from Hebbal lake show that the observed data overlap with the predicted trend based on the classification. In doing so, the drone can dynamically have a faster method of surveying and deciding the locations for sampling which will yield a better result of the overall water body assessment by deciding where the water samples should be collected from. Keywords: environmental drones, IOT, air quality, water sampling